2010
DOI: 10.1530/eje-10-0297
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping during the day: effects on the 24-h patterns of IGF-binding protein 1, insulin, glucose, cortisol, and growth hormone

Abstract: Background: Disturbed sleep is a major risk factor for metabolic disturbances, including type 2 diabetes, but the involved mechanisms are still poorly understood. We investigated how an acute shift of sleep to the daytime affected IGF-binding protein 1 (IGFBP1), which is a risk factor for diabetes. Methods: Seven healthy men (age, 22-32 years) participated in a night sleep condition (sleep 2300-0700 h) and a day sleep condition (0700-1500 h) with hourly blood samples taken for 25 h (starting at 1900 h) and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
2
13
0
2
Order By: Relevance
“…Shortened sleep or high levels of sleep duration variability may be acting as a stressor influencing cortisol output or may be representative of higher levels of stress influencing sleep behavior. This is consistent with prior studies that have demonstrated changes to 24-h patterns of cortisol in shift workers who naturally vary sleep schedules and sleep durations, as well as with studies that have experimentally manipulated sleep schedules (Rehman et al, 2010). …”
Section: Discussionsupporting
confidence: 91%
“…Shortened sleep or high levels of sleep duration variability may be acting as a stressor influencing cortisol output or may be representative of higher levels of stress influencing sleep behavior. This is consistent with prior studies that have demonstrated changes to 24-h patterns of cortisol in shift workers who naturally vary sleep schedules and sleep durations, as well as with studies that have experimentally manipulated sleep schedules (Rehman et al, 2010). …”
Section: Discussionsupporting
confidence: 91%
“…Possible contributing mechanisms for decreased EE at the beginning of the daytime sleep opportunity include reduced resting metabolic rate (31) and sleep-induced decreases in the metabolic hormones cortisol, norepinephrine, and epinephrine that typically increase EE (32,33) and are highest at this circadian time (5). During sleep, circulating cortisol, norepinephrine, and epinephrine levels are reduced and morning sleep after the nightshift could decrease these hormones (34,35), leading to decreased EE. Our finding of shorter REM latencies during daytime sleep may be associated with reduced catecholamine levels, thereby potentially decreasing EE (34).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent napping and long nap duration were shown to increase the risk of type 2 diabetes mellitus [17,18]. In in vitro experiments, sleeping during the daytime resulted in higher levels of insulin-like growth factor binding protein 1 (IGFBP1) than nocturnal sleep [19]. In addition, cell and molecular links exist between disorders of circadian rhythms and sleep with MS [20].…”
Section: Discussionmentioning
confidence: 99%